Hyperuricaemia and associated factors among the oldest-old population in the urban areas of Chengdu, China: a community-based cross-sectional study - Ya Liu; Dong Wei; Xiao-bo Huang; Wenqiang Zhang; Xiang-Ji Chen; Rui-Li Yuan; Rong-Hua Xu; Wei-Wei Tang (BMJ Open, 2021)
Objectives To investigate the prevalence of hyperuricaemia among the oldest-old persons in Chengdu and identify associated factors to provide information on achieving healthy ageing in China.DesignA community-based cross-sectional study.Setting Jinjiang, Qingyang, Longquanyi locating in the southeast, the northwest and the east of Chengdu, respectively, were chosen as the study sites.Participants A representative sample of 1391 people aged over 80 years were enrolled from September 2015 to June 2016, and 106 participants were excluded due to missing information. Thus, a total of 1285 participants were analysed in this study.Outcome measures Hyperuricaemia was defined as serum uric acid >420 µmol/L in men or serum uric acid >360 µmol/L in women. A univariable logistic regression model and a multivariable logistic regression model were used to estimate the ORs and 95% CI to explore the associated risk factors of hyperuricaemia.Results The overall prevalence of hyperuricaemia among the oldest-old was 29.6%. There was no significant sex difference in the prevalence of hyperuricaemia, 29.1% in men vs 30.0% in women (p>0.05). Hyperlipidaemia and overweight were associated with the risk of hyperuricaemia both in men (OR 1.86; 95% CI 1.27 to 2.72; OR 2.44; 95% CI 1.42 to 4.19) and in women (OR 1.78; 95% CI 1.23 to 2.58; OR 2.95; 95% CI 1.89 to 4.61). Additionally, diabetes mellitus was associated with an increased prevalence of hyperuricaemia only in women (OR 1.99; 95% CI: 1.34 to 2.97).Conclusion The burden of hyperuricaemia is substantial among the oldest-old population in the urban areas of Chengdu, China.